Penerapan Media Pembelajaran Pop Up Book dalam Kurikulum Merdeka Belajar bagi Guru-Guru Paud - Sarmauli Sarmauli; Matius Timan Herdi Ginting; Yoan Colina; Oktani Haloho (Al-Qalam Institute, 2022)
The independent learning curriculum for early childhood education is used by PAUD teachers for PAUD/TK learning. Although currently, the independent learning curriculum cannot be implemented in Tewang Sangalang Garing District, Katingan Regency, Central Kalimantan. In improving the ability of PAUD teachers, good learning media are needed so that PAUD/TK students easily understand them. One of the media used is the development of Pop Up Book media in storytelling learning. The benefit of this research is to find out how the pop-up book media in education is used by PAUD teachers for PAUD/TK learning.